Differential responses in dorsal visual cortex to motion and disparity depth cues - Arnoldussen, David M.; Goossens, Jeroen; Van Den Berg, Albert (Frontiers in Human Neuroscience, 2013)
We investigated how interactions between monocular motion parallax and binocular cues to depth vary in human motion areas for wide-field visual motion stimuli (110x100 degrees). We used fMRI with an extensive 2x3x2 factorial blocked design in which we combined two types of self-motion (translation and translation + rotation), with three categories of motion inflicted by the degree of noise (self-motion, distorted self-motion and multiple object-motion), and two different view modes of the flow patterns (stereo and synoptic viewing). Interactions between view mode and motion category revealed distinct contributions to self- and object-motion processing in 3D. For cortical areas V6 and CSv, but not the anterior part of MT+ with bilateral visual responsiveness (MT+/b), we found a disparity-dependent effect of rotational flow and noise: When self-motion perception was degraded by adding rotational flow and moderate levels of noise, the BOLD responses were reduced compared with translational self-motion alone in the synoptic view mode, but this reduction was cancelled by adding stereo information which also rescued the subject’s self-motion percept. At high noise levels, when the self-motion percept gave way to a swarm of moving objects, the BOLD signal strongly increased compared to self-motion in areas MT+/b and V6, but only for stereo in the latter. BOLD response did not increase for either view mode in CSv. These distinct response patterns indicate different contributions of areas V6, MT+/b and CSv to the processing of self-motion perception and the processing of multiple independent motions.